METHODS IN THE POST-METHODS ERA. REPORT ON AN INTERNATIONAL SURVEY ON LANGUAGE TEACHING METHODS' - Liu, Jun (International Journal of English Studies, 2009)
Do methods still have a place in 21" century language teaching? To answer this question, an international survey was conducted in the surnmer of 1999. A sample of 800 language teachers world-wide randomly drawn from 17,800 TESOLers were each given a 2-page survey. The return rate was 58.5% with the actual usable data set of448, which was analyzed by using both descriptive and inferential statistics. Among the ten commonly recognized teaching methods surveyed, both the Communicative Language Teaching Approach and an eclectic method seem to have the highest rate in familiarity, preference, and use. But when multiple factors, such as teaching contexts, instructional settings, learners' proficiency levels, class size, teaching experience and educational backgrounds of the teachers, and the status of being a native or nonnative English speaking professional were taken into consideration, various patterns and themes emerged. One interesting finding is that Grammar Translation is still used in EFL contexts, in larger classes, and with learners at low proficiency levels, though the ratio between the actual use of this method and teachers' preference does not match. Based on the results of the survey, a new theoretical framework is proposed to conceptualize language teaching methods in the post-methods era.